Il profilo personalistico dell’idealismo trascendente di Piero Martinetti - Mancini, Sandro (Filosofia, 2023)
This paper seeks to identify the space and function of the concept of “person” within Piero Martinetti’s metaphysics, with specific reference to his last and unfinished work, called by editor Emilio Agazzi “Metaphysics” or also “General Metaphysics,” constituting an extension, in the ontological sphere, of the Piedmontese philosopher’s best-known work, the “Introduction to Metaphysics.” The analysis conducted reveals the centrality of the person in Martinetti’s metaphysics and its neo-Platonic inspiration. I point out how Martinetti implements a henological foundation of the person, as opposed to the empiricist perspective, which understands the person only as a relational node. Also noted are the reasons for the proximity between Martinetti’s thought and the ontological foundation of the person operated by the metaphysics of Being, concerning Leibniz and Lotze, and also the aspects distant from it since, for Martinetti, the person extends its scope to the possible individual life after death, but does not constitute a final landing place on the path beginning with the birth of man.